Polymer Hydrogels and Their Applications Toward Sorptive Removal of Potential Aqueous Pollutants. (3rd July 2019) - Samaddar, Pallabi; Kumar, Sandeep; Kim, Ki-Hyun
Abstract: Environmental pollution is a global concern due to the rapidly increasing population and industrialization. In this context, there is a strong need to develop green separation techniques to isolate pollutants from different sources. Polymer assemblies or hydrogel polymers are water-swollen and crosslinked polymeric materials capable of retaining large amounts of water in their 3D networks. Hydrogels function as excellent adsorbents in pollutant removal processes by binding heavy metal ions and/or organic compounds due to the presence of various functional groups in their polymeric networks ( e.g ., amide, amine, and carboxylic acid). Hydrogels have the benefits of simplicity, high adsorption, and easy recovery compared to other adsorbent materials that involve activated carbon, zeolites, silica gel, biomass, and inorganic mineral. For these reasons, hydrogels have received increased interest for environmental remediation applications over the past few decades. The objective of this review is to describe the issues related to the preparation of different hydrogels, their characterization process, their adsorption characteristics for various pollutants, and the technical viability of some applications.